GAWAI DAYAK SEBAGAI KEARIFAN LOKAL PELOPOR INTEGRITAS DAN SOLIDARITAS MASYARAKAT SUKU DAYAK LEBANG - Adelbertus Beato Yulandi; F.X. Eko Armada Riyanto; Mathias Jebaru Adon (Yayasan Literasi Sains Indonesia, 2023)
The focus of this paper is to explore the value in the Dayak gawai tradition which is a pioneer of integrity and solidarity as well as the identity of the Dayak Lebang tribe. Gawai Dayak is a traditional ceremony that is routinely held every year. This is not only a form of preserving ancestral culture, but also a celebration that provides a forum or place to stay in touch with each Dayak tribe to gather and meet and deliberate together. The community wants to thank Duwato for the abundant harvest. The gratitude is realized with a big celebration accompanied by rituals of respect to the ancestral spirits (Duwato Puyanggano). To explore the Dayak gawai tradition, the author uses the literature method The purpose of this writing is to invite indigenous people to realize that this tradition does need the highest attention and respect, because its existence is also the history of life and culture of the Dayak Lebang tribe. The author finally finds that this tradition must be preserved continuously, so as not to lose its sacredness.